The relationship between serum retinol concentrations and subclinical infection in rural Brazilian children - França da Silva TELES, Laísla; de Azevedo PAIVA, Adriana; Alves LUZIA, Liania; Leite de LIMA-FERREIRA, Flávia Emília; Resende Gonçalves de CARVALHO, Cecilia Maria; de Carvalho RONDÓ, Patrícia Helen (Revista de Nutrição, 2023)
Objective To evaluate the relationship between serum retinol concentrations and subclinical infection in children from rural settlements. Methods A cross-sectional population-based study was carried out in nine rural settlements in the northeastern region of Brazil, involving 118 children aged 6 to 59 months. The relationship between serum retinol and C-Reactive Protein levels, an important marker of infectious and inflammatory processes, was investigated by multiple linear regression, controlling for demographic, socioeconomic and nutritional variables. Serum retinol and C-Reactive Protein were measured, respectively, by High Performance Liquid Chromatography and immunoturbidimetric assay in automated equipment. Results Vitamin A deficiency (retinol <0.70μmol/L) was identified in 9.3% of the children. C-Reactive Protein was the only predictor of retinol concentrations in the final regression model, causing a 0.728μmol/L reduction in retinol concentrations in the studied children (p=0.008). Conclusion Vitamin A deficiency is a problem of mild/moderate severity and measures to control infectious diseases in this population are fundamental to prevent and/or combat this problem.